Clinical correlates of “pure” essential tremor: the TITAN study - Erro, Roberto; Lazzeri, Giulia; Gigante, Angelo Fabio; Pilotto, Andrea; Magistrelli, Luca; Bologna, Matteo; Terranova, Carmen; Olivola, Enrica; Dallocchio, Carlo; Moschella, Vincenzo; Valentino, Francesca; Di Biasio, Francesca; et al. (Frontiers in Neurology, 2023)
Background To date, there are no large studies delineating the clinical correlates of “pure” essential tremor (ET) according to its new definition. Methods From the ITAlian tremor Network (TITAN) database, we extracted data from patients with a diagnosis of “pure” ET and excluded those with other tremor classifications, including ET-plus, focal, and task-specific tremor, which were formerly considered parts of the ET spectrum. Results Out of 653 subjects recruited in the TITAN study by January 2022, the data of 208 (31.8%) “pure” ET patients (86M/122F) were analyzed. The distribution of age at onset was found to be bimodal. The proportion of familial cases by the age-at-onset class of 20 years showed significant differences, with sporadic cases representing the large majority of the class with an age at onset above 60 years. Patients with a positive family history of tremor had a younger onset and were more likely to have leg involvement than sporadic patients despite a similar disease duration. Early-onset and late-onset cases were different in terms of tremor distribution at onset and tremor severity, likely as a function of longer disease duration, yet without differences in terms of quality of life, which suggests a relatively benign progression. Treatment patterns and outcomes revealed that up to 40% of the sample was unsatisfied with the current pharmacological options. Discussion The findings reported in the study provide new insights, especially with regard to a possible inversed sex distribution, and to the genetic backgrounds of “pure” ET, given that familial cases were evenly distributed across age-at-onset classes of 20 years. Deep clinical profiling of “pure” ET, for instance, according to age at onset, might increase the clinical value of this syndrome in identifying pathogenetic hypotheses and therapeutic strategies.